Beware of the employer: Financial incentives for employees may fail to prolong old age employment - Svenja Lorenz; Mona Pfister; Thomas Zwick (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
This paper shows that increasing the normal retirement age and introducing pension deductions for retirement before normal retirement age in Germany did not prolong employment of older men. The reason for this surprising result is that employers encouraged their employees to use the bridge options unemployment or partial retirement instead of the early retirement option for the long-term insured. Bridge options allowed employers to terminate employment considerably earlier than the pension for long-term insured. Employers however had to compensate their employees for the substantially higher costs of the bridge options. Therefore mainly employers with high employment adaption costs induced employees to use a bridge option during the implementation phase of the pension reform.
Keywords: J14; J18; J22; J26; 330; cohort-specific pension reform; early retirement; partial retirement; unemployment; labor supply; labor demand